Pengaruh Pemberian Tugas Rumah dalam Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa Kelas XI IPA SMA Negeri 2 Labakkang Boarding School (Materi Pokok Termokimia) - Mirnawati Mirnawati; Jusniar Jusniar; Alimin Alimin (ChemEdu, 2022)
The research is a quasi-experiment aimed to know the effect of homework in problem Based learning on critical thinking skills of students in class XI IPA SMAN 2 Labakkang Boarding School. The population was class XI IPA SMAN 2 Labakkang Boarding School which consisted of forty two students. A random sampling technique was used assuming homogeneity of students ability. The class selected as a sample was class XI IPA Albathani as an experimental class which consisted of 21 students and XI IPA Alfarizi as a control class which consisted of 21 students. The independent variable in this research was homework in problem Based learning in the experimental class and problem based learning in control class, the dependent variable was student’s critical thinking skills on thermochemical topic. Data colletion technique was obtained from student’s critical thinking skills test on posttest, which consist of 6 items essay test. The data analysis technique used are descriptive and inferential statistical analysis. The hypothesis test using t-test shows that tcalculated>ttable = 1,738 > 1,684 with α═ 0,05. So, I concluded homework in problem Based learning gave a postive effect critical thinking skillsof student in class XI IPA SMAN Labakkang Boarding School on thermochemicaltopic.